Regular fecal microbiota transplantation to Senescence Accelerated Mouse-Prone 8 (SAMP8) mice delayed the aging of locomotor and exploration ability by rejuvenating the gut microbiota - Zhang, Nana; Zhang, Yan; Wang, Zikai; Pan, Fei; Ren, Rongrong; Li, Zhengpeng; Zhao, Huijun; Luo, Xi; Li, Zongwei; Wang, Lei; Mo, Rui; Sun, Gang; et al. (Frontiers in Aging Neuroscience, 2022)
Recent evidence points out the role of the gut microbiota in the aging process. However, the specific changes and relevant interventions remain unclear. In this study, Senescence-accelerated mouse P8 (SAMP8) mice were divided into 4 groups; young-FMT-group transplanted fecal microbiota from young donors (2–3 months old) and old-FMT-group transplanted from old donors (10–11 months old); additionally, other two groups either adult mice injected with saline solution or untreated mice served as the saline and blank control groups, respectively. All mice were intervened from their 7-months-old until 13-months-old. The open field test at 9 and 11 months of age showed that the mice transplanted with gut microbiota from young donors had significantly better locomotor and exploration ability than those of transplanted with old-donors gut microbiota and those of saline control while was comparable with the blank control. 16S rRNA gene sequencing showed that the gut microbiome of recipient mice of young donors was altered at 11 months of age, whereas the alternation of the gut microbiome of old-donor recipient mice was at 9 months. For comparison, the recipient mice in the blank and saline control groups exhibited changes in the gut microbiome at 10 months of age. The hallmark of aging-related gut microbiome change was an increase in the relative abundance of Akkermansia, which was significantly higher in the recipients transplanted with feces from older donors than younger donors at 9 months of age. This study shows that fecal microbiota transplantation from younger donors can delay aging-related declines in locomotor and exploration ability in mice by changing the gut microbiome.